Analysis of Scientific Literacy Ability of Students of The Physics Education Study Program at Musamus University - Don Jaya Putra; Merta Simbolon; Aprilita Ekasari (Technium Social Sciences Journal, 2023)
Scientific literacy is defined as the ability to use scientific knowledge, identify questions, and draw conclusions based on evidence in order to understand and make decisions regarding nature and its changes due to human activities. Physics Education Department students are required to have a good level of scientific literacy. Good scientific literacy is one of the requirements for becoming a professional teacher and educator. This research was conducted with the aim of knowing the scientific literacy level of students of the Physics Education Department at Musamus University. As preliminary research (elementary research) it is hoped that this research can become the basis for subsequent research and development and can be used as a basis for making policies by interested parties. The research method used is descriptive qualitative method using inductive data analysis techniques. The research subjects were students of the Physics Education Study Program at Musamus University level one and level two for the 2022/2023 academic year. The research data was obtained through a literacy test which refers to the development of the TOSLS (Test of scientific Literacy Skills) test kit which consists of 2 indicators which are then broken down into 9 sub-indicators and then the results are analyzed using descriptive qualitative methods. The results showed: (1) The final score of scientific literacy ability of students of the Physics Education Study Program at Musamus University was 48.98 with a very low category, (2) The low scientific literacy ability of students of the Physics Education Study Program at Musamus University was caused by a lack of interest in reading, limited means and infrastructure, limited reading materials and lack of access to information technology in Merauke Regency, poor basic science at the previous level of education, physics education majors were not the desired majors, and lack of demands from lecturers to dig up a lot of information relevant to physics science.